A study of our prehistoric past from a gender perspective - Urbina-Medina, Ivel Carolina (2021)
The purpose of the research presented is to analyze and reflect on the androcentri bias with which historical disciplines have been constituted and in particular archeology, a science that studies extinct societies through their material footprints; understanding that, the repercussions of the study and the interpretationsm of our American past cause an understanding and reasoning in our present. In this sense, archeology has played a role of complicity in the reproduction and naturalization of gender stereotypes imposed in our society, which end up creating and legitimizing asymmetric relationships between individuals and groups. It is based on a bibliographical research, focused from a gender and feminist perspective, whose purpose has been to review the discussions within archaeology about gender and how this translates into archaeological practice and, as a consequence, into the understanding of our pre-Hispanic past. The purpose is further contributing with proposals and questioning that serve to apprehend and understand our historical past from a decolonial perspective, understanding that it is part of our academic work to reclaim groups historically excluded in intellectual production, in this case indigenous peoples and women and, in turn, recognize ancestral knowledge as alternatives for the construction of a society different from the current one